THE IMPORTANCE OF CONNECTED AND CONSERVED LANDSCAPES IN A TIME OF CHANGING CLIMATE (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Questions that we will answer during this Symposium include: What does the field of conservation biology tell us about unconnected, fragmented wildlife habitat? What is the solution to this problem? What are these grand designs, these "wildland networks?" What is the science behind them, and how does one go about implementing them on the ground? And how does all of this tie back in to the "elephant in the room"-a changing climate? So, what exactly is habitat fragmentation? Perhaps the simplest way to convey it is through photos (Figure 1) showing obvious swaths of forestland (which presumably still support the wildlife adapted to live in forests) adjacent to large swaths of clear-cut stubble that cannot support those species.